PENERAPAN MODEL PEMBELAJARAN TERHADAP KEMAMPUAN LITERASI NUMERASI SISWA: SYSTEMATIC LITERATURE REVIEW - Sektiwulan, Adelia; Novaliyosi; Nindiasari, Hepsi (Jurnal Riset Pembelajaran Matematika, 2024)
Numeracy literacy skills are needed in various aspects of life, whether at home, work, or in society. The importance of numeracy literacy is not aligned with the reality, which is the low level of students' numeracy literacy skills, as seen from the result of PISA 2022. Various factors affect students' numeracy literacy skills, one of which is the implementation of learning models in schools. A systematic literature review (SLR) was conducted based on 18 articles from accredited national journals in the field of mathematics education. This research focuses on two aspects, namely 1) learning models that influence numeracy literacy skills, and 2) the application of learning models at each educational level that affect numeracy literacy skills. Based on the reviewed articles, 12 learning models were found at the elementary, junior high, and senior high school levels. The learning models applied at the elementary level are PBL, STEAM, student facilitator & explaining, mind mapping, and RME. At the junior high level, the learning models are PBL, inquiry, RME, TGT, PLTL, CIRC, PjBL, TTW, and CTL, while at the senior high level, the learning models applied are peer-led team learning and problem-based learning. The results of this research can provide a summary of the literature in identifying learning models to improve students' numeracy literacy skills.